2006
DOI: 10.1016/j.febslet.2006.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced repair of DNA interstrand crosslinks in S phase

Abstract: Hela cells synchronized in G1 and S phases of the cell cycle were transfected with pEGFP crosslinked with trioxsalen. Twelve hours later the number of fluorescent cells was determined by fluorescent microscopy. Cells in S phase have repaired 0.2-0.3 ICL/kb over the 12 h period, while cells in G1 phase repaired interstrand crosslinks much more poorly. The crosslinked plasmids were efficiently recruited to the nuclear matrix both in G1 phase and S-phase, which showed that the poor repair of G1 cells was a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The examination of nucleotide excision repair (NER) and transcription coupled repair in synchronized and UV irradiated Chinese hamster ovary (CHO) cells in G1 and G2 phases identified no major differences [ 32 ]. Recent studies on synchronized Hela cells in G1 and S phases found that the S phase cells repaired DNA interstrand crosslinks more efficiently than G1-phase cells [ 33 ]. Our data has shown that there is a marked difference in BER activities in irradiated G1 and G2 enriched cells.…”
Section: Discussionmentioning
confidence: 99%
“…The examination of nucleotide excision repair (NER) and transcription coupled repair in synchronized and UV irradiated Chinese hamster ovary (CHO) cells in G1 and G2 phases identified no major differences [ 32 ]. Recent studies on synchronized Hela cells in G1 and S phases found that the S phase cells repaired DNA interstrand crosslinks more efficiently than G1-phase cells [ 33 ]. Our data has shown that there is a marked difference in BER activities in irradiated G1 and G2 enriched cells.…”
Section: Discussionmentioning
confidence: 99%
“…The ICL repair events are shown to be both replication-dependent [49] and replication-independent [50]. The replication-dependent ICL repair occurs in S or G2 phase of the cell cycle [51, 52]. ICL repair is initiated by DNA replication fork collapse which activates signaling pathways for cell cycle arrest, to repair the DNA lesion [53].…”
Section: Interstrand Crosslinks (Icls)mentioning
confidence: 99%
“…Genetic data implicate the involvement of the Ercc1-Xpf endonuclease complex of the nucleotide excision repair pathway and proteins required for homologous recombination (HR) mediated repair of double-strand breaks (DSBs) (Dronkert and Kanaar, 2001;Sancar et al, 2004). Most current models suggest that the repair of ICLs induced by photoactivated psoralens in mammalian cells occurs primarily during S-phase and that DSBs are intermediates of ICL repair (Rothfuss and Grompe, 2004;Niedernhofer et al, 2005;Mladenova and Russev, 2006). ICL formation does not trigger G1/S and G2/M checkpoints and regardless of the phase of the cell cycle during which the damage is induced, cells are arrested in S-phase (Akkari et al, 2000).…”
mentioning
confidence: 98%